A prospective observational cohort study of the efficacy of tofacitinib plus iguratimod on rheumatoid arthritis with usual interstitial pneumonia - Wang, Shuhua; Li, Yao; Tang, Yanchun; Xie, Weilin; Zhang, Yue; Liu, Qingyan (Frontiers in Immunology, 2023)
Objectives This study aims to assess the efficacy of tofacitinib (TOF) plus iguratimod (IGU) in rheumatoid arthritis (RA) with usual interstitial pneumonia (UIP) (RA-UIP). Methods This was a prospective observational cohort, single-center study. Data from 78 RA-UIP patients treated with TOF plus IGU, IGU plus conventional synthetic disease-modifying anti-rheumatic drugs (csDMARDs), and csDMARDs were analyzed. Clinically relevant responses in RA activity assessment, pulmonary function tests (PFTs), and high-resolution computed tomography (HRCT) assessment at baseline and follow-up were compared between groups to evaluate the efficacy of TOF plus IGU. Results A total of 78 patients were followed up for at least 6 months after treatment. There were significant changes in sedimentation rate (ESR), C reactive protein (CRP), and disease activity score (DAS) 28-CRP during the follow-up within each treatment group, but there was no statistically significant difference between the two groups. After 6 months of TOF plus IGU treatment, forced vital capacity (FVC)% (84.7 ± 14.7 vs. 90.7 ± 15.4) and HRCT fibrosis score (7.3 ± 3.4 vs. 7.0 ± 5.6) showed a significant improvement compared to the csDMARDs group (P = 0.031, P = 0.015). The TOF plus IGU-treated patients had a significantly higher regression and lower deterioration than the csDMARDs-treated patients (P = 0.026, P = 0.026) and had a significantly higher response (regression + stability), with overall response rates of 66.7% (16/24) vs. 35.7% (10/28) (P = 0.027), respectively. Conclusion Our results indicate that TOF plus IGU can simultaneously relieve RA and RA-UIP and be better than the csDMARDs with a higher response rate in RA-UIP, which may be a potential choice for “dual treat-to-target”.